(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Surgical site infections (SSI) are the most common nosocomial infection in surgical patients, accounting for 38% of all such infections, and are a significant source of postoperative morbidity resulting in increased hospital length of stay and increased cost. Objectives To find out the incidence of wound infection in patients following elective surgery and the most likely causative organisms and their resistance pattern. Methods Prospective data were collected on 496 surgical patients admitted in the surgery department in BSMMU from January 2010 to June 2010. All preoperative risk factors were evaluated. Patients operated were followed in the post operative period and if any wound infection noted, swab from the site of infection was sent for culture and sensitivity and antibiotics were given accordingly. Results Following 496 elective operations 20.16 % patients developed wound infection. Highest numbers of infection were seen in the fifth decade with slight female preponderance. Wound infection progressively rises with the degree of contamination and increasing operative time. The common risk factors for development of surgical wound infection were anemia (52%), malnutrition (44%), diabetes (38%), jaundice (30%), contaminated operation (44%) dirty operation (38 %), obesity and smoking. The most predominant isolated organism was Escherichia coli (43%) followed by Staphylococcus aureus (33%) and Pseudomonas aeruginosa (11%). Ceftriaxone still remains the most effective antibiotic although the incidence of resistance is rising. Conclusion Despite a good numbers of variables influence surgical site infections; it is still possible to reduce the infection rate by correcting modifiable risk factors, reducing degree of contamination and duration of operation. To battle the emerging resistance of pathogens a definitive guideline is essential. DOI: http://dx.doi.org/10.3329/jbsa.v24i2.19804 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(2): 65-69